Legal Protection For The Sustainability Of MSMEs Due To The Medan City Drainage Project - Atika Sunarto; Steven Canisius Malau; Monica Monica; Ananda Geraldine; Muhammad Ali Adnan (Eduvest - Journal of Universal Studies, 2024)
Drainage is a construction that becomes a medium for flowing water from one point to another which is considered very important to help the process of flowing water such as rainfall, so that puddles or flooding do not occur. In residential areas, drainage plays a role as a sanitation facility to avoid standing water which can disrupt environmental comfort and health, and functions to prevent flooding. MSMEs are regulated based on PP Number 7 of 2021 concerning Convenience, Protection, Empowerment of Cooperatives and MSMEs. Micro businesses are productive businesses owned by individuals or individual business entities that comply with the criteria set out in the law. Micro, Small and Medium Enterprises (MSMEs) play a significant role in Indonesia's economic development and are considered the main driver of the economy in a region. The high growth of MSMEs is certainly very encouraging because it can also reduce the unemployment rate. based on Medan Mayor Regulation No. 9 of 2009 concerning the Prohibition of Building Buildings Above Drainage Channels. Legal protection is an effort to provide protection for human rights that are harmed by other parties, as well as providing protection to the community so that they can enjoy all the rights regulated by law. In other words, legal protection includes various actions that must be taken by law enforcement officials to provide a sense of security, both mentally and physically, from interference and threats from anywhere.